A new approach to develop a climate classification for building energy efficiency addressing Chinese climate characteristics. (15th March 2020) - Bai, Lujian; Yang, Liu; Song, Bing; Liu, Na
Abstract: Defining adequate building climate zones is a fundamental step toward building energy efficiency. In this study, a new method of building climate classification for China is developed based on the climate classification method recommended by ANSI/ASHRAE standard 169–2013, and the feasibility of applying the current approach recommend by ASHRAE in China is also analyzed quantitatively. It is found that the current ASHRAE method does not distinguish between the climatic features of the drainage basin of the Yangtse River and those of the Yunnan–Guizhou Plateau. It also does not distinguish between the climatic features of the Tibetan Plateau and those across the rest of China. To address these problems, cluster analysis was adopted as a rational method to revise the current primary zone definitions. Four different climate types have been found in the new primary zones. Finally, new climate classification zones for building energy efficiency under the general climatic conditions of China were developed. The new classification method divides China into 17 climate zones and provides more detailed climate information for engineers than the current climate zone standard does. Highlights: The feasibility of the current ASHRAE method as applied in China is investigated. Cluster analysis is used to develop the zone definitions. The revised primary zone definition is raised addressing China's climate condition. A new and more detailed climate zone classification specific to China is developed.